Effectiveness and safety of self-pulling and latter transected Roux-en-Y reconstruction in totally laparoscopic distal gastrectomy - Chen, Defei; Yang, Fuyu; Woraikat, Saed; Tang, Chenglin; Qian, Kun (Frontiers in Oncology, 2022)
Background: Self-pulling and latter transection (SPLT) reconstruction has been applied in total laparoscopic total gastrectomy and BI reconstruction (known as Delta SPLT) in total laparoscopic distal gastrectomy (TLDG) in some previous studies. This approach can reduce the technical difficulty of the surgery as well as the quantity of cartridges required, with manageable safety. Here, we used SPLT to complete Roux-en-Y reconstruction in TLDG and evaluated the safety and effectiveness of this novel method by comparing it with conventional Roux-en-Y reconstruction in laparoscopy-assisted distal gastrectomy (LADG). Methods: Patients with gastric cancer who underwent SPLT-TLDG or LADG between June 2019 and September 2021 were retrospectively analyzed. Baseline information and postoperative short-term surgical outcomes of the two groups were compared. Results A total of 114 patients with gastric cancer were included in the study. Patients underwent SPLT-TLDG (n = 73, 64.0%) or LADG (n = 41, 36.0%). No patient underwent open surgery. There were no differences in patient demographics or tumor characteristics between the two groups. The mean intraoperative blood loss was 47.1 ± 34.3 ml in the SPLT-TLDG group, which was significantly less than that in the LADG group (P = 0.022). There were no significant differences in operation time, harvested lymph nodes, time to first flatus, time to liquid intake, or postoperative hospital stay between the two groups. Nine and five patients had short-term postoperative complications in the SPLT-TLDG and LADG group, respectively. Conclusion: We introduced a self-pulling and latter transected Roux-en-Y reconstruction (SPLT-RY) for use in TLDG. We showed that SPLT-RY reconstruction in TLDG is a safe and feasible surgical method in terms of short-term surgical outcomes and has the advantages of simplifying the reconstruction.